Microsaccade generation requires a foveal anchor - Jorge Otero-Millan; Rachel E Langston; Francisco Costela; Stephen L Macknik; Susana Martinez-Conde (Bern Open Publishing, 2020)
Visual scene characteristics have the ability to affect various aspects of saccade and microsaccade dynamics. For example, blank visual scenes are known to elicit diminished saccade and microsaccade production, compared to natural scenes. Similarly, microsaccades are less frequent in the dark. Yet, the extent to which foveal and peripheral visual information contribute to microsaccade production remains unclear: because microsaccade are directed to covert attention locations as per the superior colliculus activation map, it follows that peripheral stimulation could suffice to produce regular microsaccade dynamics, even without foveal stimulation being present. Here we compared the characteristics of microsaccades generated in the presence or absence of foveal and/or peripheral visual stimulation, while human subjects conducted four types of oculomotor tasks (fixation, free-viewing, guided-viewing and fixation during passive viewing). Foveal information was either available, or made unavailable by the presentation of both solid and blurred scotomas. We found foveal stimulation to be critical for microsaccade production, and peripheral stimulation, by itself, to be insufficient to yield microsaccades. Our results indicate that a foveal visual anchor is necessary for microsaccade generation.